Stress responsive OsHyPRP16 promoter driven early expression of resistance gene Pi54 potentiate the resistance against Magnaporthe oryzae in transgenic rice. (November 2022) - Kapoor, Ritu; Kumar, Gulshan; Pawar, Lata; Salvi, Prafull; Devanna, Basavantraya N.; Singh, Kashmir; Sharma, Tilak Raj
Abstract: The rice Hybrid Proline Rich Protein (HyPRP) encoding gene, OsHyPRP16 expression exhibit early upregulation in response to Magnaporthe oryzae inoculation. Here, we functionally characterized the OsHyPRP16 promoter through deletion analysis in transgenic Arabidopsis using GUS (β-glucuronidase) reporter assay. The promoter fragments, sequentially deleted from the 5′ end could induce differential GUS activity in response to stresses induced by different hormones and abiotic stress conditions. In addition, a strong GUS induction was observed in M. oryzae inoculated transgenic Arabidopsis. Based on the insilico and stress-inducibility of D1 promoter fragment against various phytohormones and rice blast fungus, and with no basal activity under control conditions, we rationally selected D1 promoter fragment to drive the expression of a major rice blast resistance gene; Pi54 in the genetic background of blast susceptible TP309 rice line. The D1 promoter fragment was able to induce the expression of Pi54 at immediate-early stages of M. oryzae infection in transgenic rice. The transgenic plants with Pi54 under the control of D1 promoter fragment displayed complete resistance against M. oryzae infection as compared to control plants. The present study suggests that the D1 fragment of OsHyPRP16 promoter is a valuable tool for breeding and development of rice lines with early-inducible and pathogen-responsive enhanced disease resistance. Highlights: Functional characterization of rice HyPRP16 promoter was performed. Deletion fragment (D1) exhibits distinct stress-response with no basal activity. D1 driven R gene ( Pi54 ) induce early upon M. oryzae infection in transgenic rice. Early induction of Pi54 impart resistance against rice blast disease.